1992
DOI: 10.1093/oxfordjournals.eurheartj.a060113
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after recovery from myocardial infarction: the relative importance of cardiac dilatation and coronary stenoses

Abstract: In order to further define clinical and angiocardiographic predictors of long-term survival after myocardial infarction we followed 616 consecutive male patients under 60 years of age, survivors of a first (N = 455) or recurrent (N = 161) myocardial infarction, for 8.8 +/- 2.9 years. Patients had angiocardiography at 4-8 weeks after infarction; none had thrombolysis, but 33% had cardiac surgery, 14% on a clinical trial basis. Left ventricular end-systolic volume was the most powerful predictor of cardiac morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Interobserver agreement for EF showed high intraclass correlation for 64-row CT, MRI, 2D Echo, and 3D Echo (intraclass correlation coefficient Ͼ0.8), whereas agreement was lower for CVG (intraclass correlation coefficient ϭ 0.58). Left ventricular (LV) function is an important factor in terms of patient management, outcome, and long-term survival of patients with cardiac disease (1,2). Several diagnostic methods are available to evaluate LV function, among which 2-dimensional echocardiography (2D Echo) is the most widely used because it offers fast, relatively inexpensive, and noninvasive functional analysis without radiation exposure or contrast medium administration.…”
Section: Resultsmentioning
confidence: 99%
“…Interobserver agreement for EF showed high intraclass correlation for 64-row CT, MRI, 2D Echo, and 3D Echo (intraclass correlation coefficient Ͼ0.8), whereas agreement was lower for CVG (intraclass correlation coefficient ϭ 0.58). Left ventricular (LV) function is an important factor in terms of patient management, outcome, and long-term survival of patients with cardiac disease (1,2). Several diagnostic methods are available to evaluate LV function, among which 2-dimensional echocardiography (2D Echo) is the most widely used because it offers fast, relatively inexpensive, and noninvasive functional analysis without radiation exposure or contrast medium administration.…”
Section: Resultsmentioning
confidence: 99%
“…Although focus on EF could suggest that LV function was only moderately impaired at baseline (after infarction), analysis of LV volumes at the same time point shows that they were dramatically enlarged compared with healthy hearts, 32,33 which makes the 4-month attenuation of remodelling yielded by the cells+fibrin patch functionally relevant, particularly if one keeps in mind that LVESV has been reported to be a strong predictive factor of outcome in patients following a myocardial infarction. 34 In keeping with these data, the cell-scaffold product also achieved the lowest value of the heart failure index generated by combining genomic and functional end points associated with heart failure, 35 cardiomyopathy 36 and adverse LV remodelling. 37 Overall, these results are consistent with those previously reported with the use of fibrin used either in an injectable form mixed with skeletal myoblasts 38 or bone marrow-derived cells 28,39 or as an epicardial patch loaded with mouse ESC-derived BMP-2-treated cardiac progenitors 40 The mechanism of the incremental benefit afforded by the cell-loaded fibrin patch remains to be investigated.…”
Section: Interpretation Of Outcomesmentioning
confidence: 64%
“…Along with neurohormonal activation, these changes lead to maladaptive LV remodeling and progressive deterioration of the remaining myocardium 38. Prior studies, which have shown that increased ESV post-MI is associated with increased mortality,6,39,40 indicate that larger ESV is an important predictor of adverse events in patients with CHD. In addition, reduction in ESV has been associated with improved mortality, reduced HF symptoms, and improved quality of life in cardiac resynchronization trials 41…”
Section: Discussionmentioning
confidence: 99%